Design of a lightweight universal talus implant using topology optimization - Hafez, Ahmed H.; El-Rich, Marwan; Liu, Tao; Jomha, Nadr; Schiffer, Andreas (Frontiers in Bioengineering and Biotechnology, 2023)
Total talus replacement is a promising alternative treatment for talus fractures complicated by avascular necrosis and collapse. This surgical option replaces the human talus bone with a customized talus implant and can maintain ankle joint functionality compared to traditional treatment (e.g., ankle fusion). However, the customized implant is costly and time-consuming due to its customized nature. To circumvent these drawbacks, universal talus implants were proposed. While they showed clinically satisfactory results, existing talus implants are heavier than biological talus bones as they are solid inside. This can lead to unequal weight between the implant and biological talus bone, and therefore leading to other complications. The reduction of the implants’ weight without compromising its performance and congruency with surrounding bones is a potential solution. Therefore, this study aims to design a lightweight universal talus implant using topology optimization. This is done through establishing the loading and boundary conditions for three common foot postures: neutral, dorsi- and plantar-flexion. The optimized implant performance in terms of mass, contact characteristics with surrounding joint cartilage and stress distributions is studied using a 3D Finite Element (FE) model of the ankle joint. The mass of the optimized implant is reduced by approximately 66.6% and its maximum stresses do not exceed 70 MPa, resulting in a safety factor of 15.7. Moreover, the optimized and solid implants show similar contact characteristics. Both implants produced peak contact pressures that were approximately 19.0-196% higher than those produced by the biological talus. While further mechanical testing under in-vivo loading conditions is required to determine clinical feasibility, preliminarily, the use of a lightweight universal implant is expected to provide the patient with a more natural feel, and a reduced waiting period until surgery.